2020
DOI: 10.1007/s00191-020-00701-8
|View full text |Cite
|
Sign up to set email alerts
|

Time to exit: “revolving door effect” or “Schumpeterian gale of creative destruction”?

Abstract: Over the past decades, exit has been analyzed at the theoretical and empirical levels. From this rich series of contributions, two basic patterns of exit can be identified: the revolving door and the gale of creative destruction. In the first, the liability of newness plays a major role in the exit process, while in the second the displacement of non-innovators is the driver of exit. We have tested these two patterns of exit on the population of Dutch firms that exited in 2018. We find confirmation that the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…All five cases explored in this study showed an appreciation of the value of motivated, skilled staff able to turn their hand to the fluctuating requirements of the fast-growing firm. More research is needed to explore the pivotal importance or otherwise of HR maturity as opposed to (for example) innovation (Cefis et al. , 2021) in determining long-time survival of a group of firms facing staff churn.…”
Section: Discussionmentioning
confidence: 99%
“…All five cases explored in this study showed an appreciation of the value of motivated, skilled staff able to turn their hand to the fluctuating requirements of the fast-growing firm. More research is needed to explore the pivotal importance or otherwise of HR maturity as opposed to (for example) innovation (Cefis et al. , 2021) in determining long-time survival of a group of firms facing staff churn.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the focus here was on limited companies (due to potential issues in comparing financial information between legal forms; see Statistics Finland, 2019). Evidence from the firm exit context (Cefis et al, 2021) indicates, however, that firm performance patterns with age may differ between legal forms. Lastly, the start dates used in the firm age calculation link to firm identifier codes in the source data.…”
Section: Size-related Findings In More Detailmentioning
confidence: 99%
“…Research focus has largely remained on an individual's decision to enter the venture creation process and not on how an individual's characteristics relate to entrepreneurial exit decisions (Kerr, Kerr and Xu, 2017), even when new venture initiatives are exposed to high risk of infant exit (Cefis et al, 2021); around half of the new ventures initiatives cease during the entrepreneurial process (Hammer, 2019;Cueto, Suárez and Mayor, 2020); and at least half of all nascent ventures never reach a stage where they can recoup their start-up costs (Parker and Belghitar, 2006). In other words, most nascent entrepreneurs do not succeed in launching their ventures and decisions to exit the entrepreneurial process are a frequent phenomenon (Lukeš and Zouhar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…although it has been analysed both from the theoretical and empirical perspective, these have mostly considered the firm-level perspective (Cefis et al, 2021;Cefis et al, 2020;Coad, Frankish and Storey, 2020;Coad et al, 2013), including time to firm's exit (Elfenbein and Knott, 2015). Moreover, the venture exit decision has been considered the flip side of venture persistence (Zhu et al, 2018) in presence of start-up challenges and other available alternatives (Holland and Shepherd, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation